Fabp1 gene ablation inhibits high‐fat diet‐induced increase in brain endocannabinoids. Issue 2 (29th November 2016) - Martin, Gregory G.; Landrock, Danilo; Chung, Sarah; Dangott, Lawrence J.; Seeger, Drew R.; Murphy, Eric J.; Golovko, Mikhail Y.; Kier, Ann B.; Schroeder, Friedhelm
Abstract : Fatty acid binding protein‐1 (FABP‐1) is not detectable in brain but is highly expressed in liver. FABP‐1 null (LKO) male mice on control, but not high‐fat, diet had increased brain levels of arachidonic acid‐containing endocannabinoids (AEA, 2‐AG), correlating with increased free and total arachidonic acid in brain and serum; however, this dietary phenomenon was not observed in female LKO. Abstract: The endocannabinoid system shifts energy balance toward storage and fat accumulation, especially in the context of diet‐induced obesity. Relatively little is known about factors outside the central nervous system that may mediate the effect of high‐fat diet (HFD) on brain endocannabinoid levels. One candidate is the liver fatty acid binding protein (FABP1), a cytosolic protein highly prevalent in liver, but not detected in brain, which facilitates hepatic clearance of fatty acids. The impact of Fabp1 gene ablation (LKO) on the effect of high‐fat diet (HFD) on brain and plasma endocannabinoid levels was examined and data expressed for each parameter as the ratio of high‐fat diet/control diet. In male wild‐type mice, HFD markedly increased brain N‐acylethanolamides, but not 2‐monoacylglycerols. LKO blocked these effects of HFD in male mice. In female wild‐type mice, HFD slightly decreased or did not alter these endocannabinoids as compared with male wild type. LKO did not block the HFD effects in female mice. The HFD‐induced increase in brain arachidonic acid‐derived arachidonoylethanolamide in males correlated with increased brain‐free and total arachidonic acid. The ability of LKO to block the HFD‐induced increase in brain arachidonoylethanolamide correlated with reduced ability of HFD to increase brain‐free and total arachidonic acid in males. In females, brain‐free and total arachidonic acid levels were much less affected by either HFD or LKO in the context of HFD. These data showed that LKO markedly diminished the impact of HFD on brain endocannabinoid levels, especially in male mice.